Association between the habit of reading food labels and health-related factors in elderly individuals of the community - VERÍSSIMO, Ana Carolina; de Albuquerque BARBOSA, Maria Cristina; Araújo Vieira ALMEIDA, Nizia; Carrenho QUEIROZ, Andreia Cristiane; Gendzelevki KELMANN, Regina; Lima Alvares da SILVA, Clarice (Revista de Nutrição, 2023)
Objective To investigate the association between the habit of reading food labels and health related factors in elderly individuals who are members of social groups in the city of Governador Valadares, in the state of Minas Gerais, Brazil. Methods This cross-sectional study interviewed 141 individuals, members of elderly social groups. The socioeconomic and health profile was defined based on sex, age, marital status, educational level, disease occurrence, use of medication, physical exercise and self-perception of health. The habit of reading the food labels was assessed through the question: “Do you read the food label before purchasing or consuming the product?”. In case of an affirmative answer, researchers asked which items from the labels were observed by the individual. Weekly food intake was assessed through a food frequency questionnaire and classified in scores. The anthropometric evaluation was based on the calculation and classification of the Body Mass Index. A multinomial logistic regression was used to determine factors associated with the habit of reading the labels, and it was considered significant when p<0.025. Results The habit of reading labels was reported by 72.3% of the participants, whom predominantly verified the product’s expiration date (90.2%), followed by the amount of fat (18.4%) and sodium (16.7%) in it. This behavior was independently associated with a lower mean consumption of medicines, a lower per capita household consumption of sugar and a higher weekly frequency of per capita whole grain consumption. Conclusion The habit of reading the food labels is associated with a better health condition and with a healthier eatingbehavior among elderly individuals and it should be considered as an important nutritional strategy in this age group.